Perioperative chemotherapy for muscle‐invasive bladder cancer: A population‐based outcomes study. Issue 11 (14th April 2014) - Booth, Christopher M.; Siemens, D. Robert; Li, Gavin; Peng, Yingwei; Tannock, Ian F.; Kong, Weidong; Berman, David M.; Mackillop, William J.
Abstract : BACKGROUND: Practice guidelines recommend neoadjuvant chemotherapy (NACT) for bladder cancer. However, the evidence in support of adjuvant chemotherapy (ACT) is less robust. Here we describe whether the evidence of efficacy for NACT/ACT was sufficient to change clinical practice and whether the efficacy demonstrated in clinical trials was translated into effectiveness in the general population. METHODS: Electronic records of treatment were linked to the population‐based Ontario Cancer Registry to identify all patients with bladder cancer treated with cystectomy in Ontario 1994‐2008. Utilization of NACT/ACT was compared across 1994‐1998, 1999‐2003, and 2004‐2008. Logistic regression was used to analyze factors associated with NACT/ACT. Cox model and propensity score analyses were used to explore the association between ACT and survival. RESULTS: Two thousand forty‐four patients underwent cystectomy for muscle‐invasive bladder cancer (MIBC). Use of NACT remained stable (mean, 4%), whereas utilization of ACT increased over time (16%, 18%, 22%; P  = .001). Advanced stage (T3/T4; OR, 1.83; 95% CI, 1.38‐2.46) and node‐positive disease (OR, 8.10; 95% CI, 6.20‐10.7) were associated with greater utilization of ACT. Five‐year overall survival (OS) and cancer‐specific survival (CSS) for all patients was 29% (95% CI, 28%‐31%) and 33% (95% CI, 31%‐35%), respectively. Utilization of ACT was associated with improved OS (HR, 0.71; 95% CI, 0.62‐0.81) and CSS (HR, 0.73; 95% CI, 0.64‐0.84). Results were consistent in propensity score analyses. CONCLUSIONS: NACT remains substantially underutilized in routine clinical practice. Our results suggest that perioperative chemotherapy is associated with a substantial survival benefit in the general population. Patients who are planning to undergo cystectomy for bladder cancer should be reviewed by a multidisciplinary team. Cancer 2014;120:1630–1638 . © 2013 American Cancer Society . Abstract : Perioperative chemotherapy remains underutilized in routine clinical practice. The results of this large contemporary population‐based study suggest that adjuvant chemotherapy is associated with substantial improvement in the general population.